Genetic susceptibility to hip arthroplasty failure—association with the RANK/OPG pathway - Malik, M. H.A. (Springer-Verlag, 2006)
The OPG/RANK/RANKL system has been implicated in the biological cascade of events initiated by particulate wear debris and bacterial infection resulting in periprosthetic bone loss around total hip arthroplasties (THA). Individual responses to such stimuli may be dictated by genetic variation caused by single nucleotide polymorphisms (SNPs). Case control study of the osteoprotegerin and RANK genes for possible association with deep sepsis or aseptic loosening. All patients were Caucasian and had had a cemented Charnley THA and polyethylene acetabular cup. Cases consisted of 91 patients with early aseptic loosening and 71 patients with deep infection. Controls were 150 clinically and radiologically well-fixed THAs. DNA samples were genotyped using Taqman allelic discrimination. The A allele (p<0.001) and genotype A/A (p<0.001) for the OPG-163 SNP were associated with aseptic failure. Additionally, the RANK +575 (C/T SNP) T allele (p=0.004) and T/T genotype (p=0.008) frequencies were associated with aseptic failure. Comparing the septic group with the controls, the frequency of the A allele (p<0.001) and the genotype A/A (p<0.001) for the OPG-163 SNP were statistically significant. Aseptic loosening and deep infection of THA may be under the influence of susceptibility genes. SNP markers may serve as predictors of implant survival.